AI-Enabled Orthodontic Telehealth And Endodontic Sterilization: Knowledge And Practices Of Dental Assistants And Nurses Under Saudi Vision 2030 (The Review of Diabetic Studies, 2024)
Background: The integration of artificial intelligence (AI) in orthodontic telehealth and the reinforcement of endodontic sterilization protocols represent critical advances in modern dentistry. These developments are particularly relevant in Saudi Arabia, where healthcare transformation under     Vision 2030 emphasizes digital innovation, patient safety, and workforce empowerment                                                                                                                                              Objective: This narrative review explores the knowledge and practices of dental assistants and nurses regarding AI-enabled orthodontic telehealth and endodontic sterilization. It highlights their role in supporting digital health initiatives and infection control within the Saudi context.                                                                                                                                                       Methods: A structured search of PubMed, Scopus, Web of Science, and Google Scholar was conducted for studies published between 2015 and 2025. Keywords included “artificial intelligence,” “orthodontic telehealth,” “endodontic sterilization,” “infection control,” “dental assistants,” “nurses,” and “Saudi Arabia.” Peer-reviewed articles, guidelines, and systematic reviews were included, with findings synthesized thematically.                                                                                                                            Results: The literature demonstrates that AI-driven orthodontic telehealth enhances diagnostic accuracy, facilitates remote monitoring, and reduces healthcare disparities, while sterilization protocols in endodontics remain indispensable for ensuring patient safety. However, evidence indicates gaps in training and inconsistent compliance among dental auxiliaries. Dental assistants and nurses require targeted upskilling in AI literacy, digital workflows, and infection control to fully realize the benefits of these innovations.                                                                                                                                       Conclusion: Aligning AI-enabled orthodontic telehealth and rigorous endodontic sterilization with Saudi Vision 2030 will strengthen the national dental workforce, improve patient safety, and promote global competitiveness in healthcare. Empowering dental assistants and nurses through structured training and regulatory support is essential to achieve these objectives.